The complete mitochondrial genome of the deep-water cartilaginous fish Hydrolagus affinis (de Brito Capello, 1868) (Holocephali: Chimaeridae) - André Gomes-dos-Santos; Nair Vilas Arrondo; André M. Machado; Ana Veríssimo; Montse Pérez; Esther Román; L. Filipe C. Castro; Elsa Froufe (Mitochondrial DNA. Part B. Resources, 2020)
Cartilaginous fishes are a highly vulnerable vertebrate group but remain poorly studied, especially those occupying deep-water ecological niches. Here, we describe the complete mitogenome of the deep-water chimaeriform Hydrolagus affinis (de Brito Capello, 1868) (Holocephali: Chimaeridae). The mitogenome has 19,437 nucleotides and the same overall content, i.e. 13 protein-coding genes, 22 transfer RNA, 2 ribosomal RNA genes, as available for all cartilaginous fishes mitogenomes. Phylogenetic reconstructions including 615 cartilaginous fishes mitogenomes place the H. affinis within the family Chimaeridae but suggest that Hydrolagus and Chimera are not reciprocally monophyletic, highlighting the need for additional molecular data to improve phylogenetic reconstruction.